Investigating the antecedents and consequences of e-participation on refugees sustainable livelihoods a case: Palestinian refugees in the Gaza strip - Aradeh, Osama Aabid (Department of Information Systems, 2023)
The use of Information and Communications Technology (ICT) has advanced in all socioeconomic strata, especially in developing countries. The use of ICT has had a significant impact on the participation of civilians, both citizens and refugees in the context of politics. In addition, ICTs have enabled innovative forms of participation, both in terms of participation channels and the outcomes of participatory processes. However, studies on the impact of electronic participation on the livelihoods of vulnerable and marginalized groups, and public service providers are limited. This study investigated the role of e-participation implementation on improving and sustaining of refugees' livelihoods in developing countries, precisely the Gaza Strip in Palestine. This study used a mixed-method approach of qualitative and quantitative research. The quantitative approach was utilized to examine the perspectives of Palestinian refugees in the Gaza Strip, using a survey conducted to collect statistical information. 281 questionnaires were collected from Palestinian refugees over the age of 18. Furthermore, qualitative approach was carried out in an inductive approach by means of individual in-depth semi-structured interviews with public service providers in the Gaza Strip, such as of water supply, electricity, housing and infrastructure in their daily lives. Seven organizations with 19 interviews, including four municipalities, two nongovernmental organizations and one international organization, the United Nations Relief and Works Agency for Palestine refugees in the near east (UNRWA), participated. The literature and findings of this study provided a more comprehensive insight from the perspective of public services providers and refugees related to antecedents and consequences of e-participation influencing the sustainable livelihoods of refugees in the Gaza Strip, Palestine. This study therefore diverts some the attention of around the political context to an ICT-based participation phenomenon in developing countries' livelihoods. In conclusion, this research was intended to provide theoretical and practical contributions. In theoretical terms and the context of e-participation between service providers and vulnerable groups such as refugees, the conceptual research framework can serve as basis for Information Systems researchers. In practical terms, this research study has tangible implications for understanding the contributions of using electronic participation channels to improve livelihoods of other similar groups inside or outside Palestine.